A novel cyclic peptide targeting LAG-3 for cancer immunotherapy by activating antigen-specific CD8+ T cell responses - Wenjie Zhai; Xiuman Zhou; Hongfei Wang; Wanqiong Li; Guanyu Chen; Xinghua Sui; Guodong Li; Yuanming Qi; Yanfeng Gao (Elsevier, 2020)
PD-1 and CTLA-4 antibodies offer great hope for cancer immunotherapy. However, many patients are incapable of responding to PD-1 and CTLA-4 blockade and show low response rates due to insufficient immune activation. The combination of checkpoint blockers has been proposed to increase the response rates. Besides, antibody drugs have disadvantages such as inclined to cause immune-related adverse events and infiltration problems. In this study, we developed a cyclic peptide C25 by using Ph.D.-C7C phage display technology targeting LAG-3. As a result, C25 showed a relative high affinity with human LAG-3 protein and could effectively interfere the binding between LAG-3 and HLA-DR (MHC-II). Additionally, C25 could significantly stimulate CD8+ T cell activation in human PBMCs. The results also demonstrated that C25 could inhibit tumor growth of CT26, B16 and B16-OVA bearing mice, and the infiltration of CD8+ T cells was significantly increased while FOXP3+ Tregs significantly decreased in the tumor site. Furthermore, the secretion of IFN-γ by CD8+ T cells in spleen, draining lymph nodes and especially in the tumors was promoted. Simultaneously, we exploited T cells depletion models to study the anti-tumor mechanisms for C25 peptide, and the results combined with MTT assay confirmed that C25 exerted anti-tumor effects via CD8+ T cells but not direct killing. In conclusion, cyclic peptide C25 provides a rationale for targeting the immune checkpoint, by blockade of LAG-3/HLA-DR interaction in order to enhance anti-tumor immunity, and C25 may provide an alternative for cancer immunotherapy besides antibody drugs.